The change of auditor: the portuguese case - Heliodoro, Paula (2018)
Submitted by Marta Frade (marta.diogo@ess.ips.pt) on 2018-02-07T10:30:45Z No. of bitstreams: 1 2-2016-The Change of Auditor.pdf: 203554 bytes, checksum: 6006441e45cf27ef910beaf48672d5c8 (MD5)